Pengaruh Estetika pada Feeds Instagram terhadap Brand Image @wmdfashion - Tisatuladiah Gustian F; David Rizar Nugroho; Enden Darjatul Ulya; Mulyono Mulyono (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study analyzes the influence of visual aesthetics on Instagram feeds in shaping the brand image of @wmdfashion among its followers. In the digital era, visual presentation has become a key factor in how audiences perceive fashion brands, particularly through elements such as color consistency, layout, visual style, and content creativity. This research employs a quantitative approach using an online survey distributed to 100 active followers of @wmdfashion. A Likert-scale questionnaire was used to measure perceptions related to feed aesthetics and brand image. The data were analyzed descriptively and through simple linear regression to examine the effect of the independent variable on the dependent variable. The findings show that Instagram feed aesthetics have a positive and significant impact on brand image, indicating that visually consistent and appealing content strengthens perceived quality, brand associations, and consumer trust. These results underscore the strategic importance of visual branding for local fashion businesses in enhancing audience engagement and building a favorable digital brand image.